THE IMPACT OF THE TURKIC CULTURAL HERITAGE ON JOINT PROJECTS IN THE FIELD OF DECORATIVE AND APPLIED ARTS OF UZBEKISTAN AND TURKEY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article explores the influence of Turkic cultural heritage on joint projects in the field of decorative arts between Uzbekistan and Turkey. The focus is on traditional motifs, crafts, and ornaments that are reflected in joint exhibitions and festivals. Special attention is given to how cultural ties between the two countries are expressed through artistic practices, which enhances mutual understanding and helps preserve traditions. The paper highlights the role of cultural initiatives as an important mechanism for diplomatic and educational interaction.